Diseño de una matriz de decisión de un fluido de limpieza y estimulación en un pozo inyector del campo la Cira Infantas (2018)
The objective of the project is to develop a decision matrix for a cleaning and stimulation fluid in an injector well in the La Cira Infantas Field. For this purpose, a geological description of the Middle Valley Basin of Magdalena was carried out. find the field of study, as well as the presentation of the stratigraphic column, the access roads to the field and in the same way its history of production and development. The following describes everything related to water injection, since the The matrix is focused on a water injector well and the completion of them is explained with selective strings which is the configuration that predominates in the injector wells of the field. Once the injection wells have been completed, the problems that can occur in a water injector well are detailed and subsequently the problems that cause the decrease in the efficiency of the water injection in the La Cira Infantas field are specified. which is a fundamental data for the development of the decision matrix.